CPT1A mediated preservation of mitochondrial inhibits pyroptosis in pancreatic acinar cells - Liu, Yijiang; Liu, Yangbo; Yu, Xiuxian; Tian, Simin; Li, Xiaojuan; Gao, Yu; Bao, Xin; Wu, Xiaoyi; Zhang, Boli; Huang, Wen (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCarnitine palmitoyltransferase 1A (CPT1A) is crucial for mitochondrial function, and its dysfunction has been linked to the development of several diseases. However, the role of CPT1A in severe acute pancreatitis (SAP) and its underlying mechanisms remain unclear. Mitochondrial damage-mediated pyroptosis has been identified as a critical factor in pancreatic acinar cell death during SAP. this study aimed to evaluate the protective role of CPT1A in SAP and investigate its association with pancreatic acinar cell pyroptosis.MethodsSAP models were established in male C57BL/6 mice by retrograde injection of 3% sodium taurocholate (STC) into the pancreatic duct and in primary acinar cells treated with 5 mM STC. Changes in Cpt1a mRNA and protein expression were assessed. Pancreatic pyroptosis was evaluated via activation of NLRP3 inflammasome-related proteins. Cpt1a was knocked down (siRNA) or inhibited (etomoxir) in cells. Cell viability was measured using Hoechst/PI staining, western blotting, and LDH release assays. The effects of CPT1A activators (C75, L-carnitine(LC)) on mitochondrial function (ΔΨm, mtROS, ox-mtDNA release) were examined in acinar cells.ResultsIn STC-induced SAP models (in vivo and in vitro), CPT1A expression was downregulated. Activating CPT1A with C75 or LC protected mitochondrial function (preserving ΔΨm, reducing mtROS, inhibiting ox-mtDNA release), thereby suppressing pyroptosis. LC treatment alleviated SAP in mice by inhibiting the NLRP3/GSDMD/Caspase-1 pathway and reducing acinar cell pyroptosis.DiscussionThese findings reveal a novel protective mechanism of CPT1A in SAP. Enhancing CPT1A activity preserves mitochondrial functions and suppresses NLRP3/GSDMD-mediated pancreatic acinar cell pyroptosis, highlighting CPT1A as a potential therapeutic target.